Novel psychoactive substance consumption is more represented in bipolar disorder than in psychotic disorders: A multicenter‐observational study. (18th May 2017) - Acciavatti, Tiziano; Lupi, Matteo; Santacroce, Rita; Aguglia, Andrea; Attademo, Luigi; Bandini, Laura; Ciambrone, Paola; Lisi, Giulia; Migliarese, Giovanni; Pinna, Federica; Quattrone, Diego; Ribolsi, Michele; et al.
Abstract: Objective: Comorbidities between psychiatric diseases and use of traditional substances of abuse are common. Nevertheless, there are few data regarding the use of novel psychoactive substances (NPS) among psychiatric patients. Aim of this multicentre survey is to investigate the consumption of a number of psychoactive substances in a young psychiatric sample. Methods: Between December 2013 and September 2015, a questionnaire was administered in 10 Italian psychiatric care facilities to a sample of 671 patients, aged 18–26 (mean age 22.24; SD 2.87). Results: About 8.2% of the sample declared to have used NPS at least once, and 2.2% had consumed NPS in the previous 3 months. The three psychiatric diagnoses most frequently associated with NPS use were bipolar disorder (23.1%), personality disorders (11.8%), and schizophrenia and related disorders (11.6%). In univariate regression analysis, bipolar disorder was positively associated with NPS consumption, an association that did not reach statistical significance in the multivariate analysis. Conclusions: The use of NPS in a young psychiatric population appears to be frequent, and probably still underestimated. Bipolar disorder shows an association with NPS use. Careful and constant monitoring and an accurate evaluation of possible clinical effects related to NPS use are necessary.